Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV SONNE during cruise SO304 - Volkhard Spieß; Tilmann Schwenk; Elda Miramontes; Till J J Hanebuth; Nikolas Römer-Stange; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV SONNE during cruise SO304 using a Kongsberg EM 710 multibeam echosounder. The expedition took place during 22.02.2024 - 07.04.2024 from Colombo (Sri Lanka) to Colombo (Sri Lanka) in the Gulf of Bengal. The major aim of SO304 is to understand the interplay of Monsoon, Cyclones, Tectonics, Subsidence and Anthropogenic Impact on the Bengal Shelf as critical Land-Ocean-Atmosphere Interface and Archive. Data were recorded within the EEZ of Bangladesh only beyond 300m water depth. Sound velocity profiles (SVP) were applied on the data for calibration. Please see the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data provision are part of the DAM Underway Project and published according to the FAIR principles.